Five urban trees causing severe damage to cities (2010)
This article brings forward a reflection on five species that are currently part of the urban tree population of many Colombian cities and towns that, nevertheless, have been reported to cause severe damage to architectural constructions, civil works, residential utilities infrastructure and public lighting on the urban space: the Weeping Fig (Ficus benjamina), the Rubber Fig (Ficus elastica), the Flame Tree (Delonix regia), the Breadfruit Tree (Artocarpus communis) and the African Tulip Tree (Spathodea campanulata). The paper concludes that such species should not be planted in public and/or private urban green spaces in Colombian cities and towns, due to the severe and costly damages that their aggressive roots may cause.